Detecting students’ misconception in simple harmonic motion concepts using four-tier diagnostic test instruments - Tumanggor, Awal Mulia Rejeki; Supahar, Supahar; Ringo, Ernila Siringo; Harliadi, Muhammad Dika (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2020)
This research aims to develop the test instrument that is feasible in terms of validity, reliability, and difficulty level and to identify students' misconceptions in simple harmonic motion concepts. The development stages used in this research were the modifications result from Oriondo & Dalo-Antonio, which included: (1) planning and design development, (2) trying out, and (3) measurement and interpretation of results. The instrument has been developed and categorized as effective because it is declared valid and reliable based on the criteria of the lowest and highest limit of the INFIT MNSQ which is 0.77 and 1.30, all test items are fitted with the PCM model, and the instrument's reliability has an item reliability value of 0.73 with a good category. The test instrument was applied to 60 students of the tenth-grade of senior high school. Based on the results, the four-tier test instrument developed was able to identify students' conceptual understanding of 36.4%, and 17.7% of students only understood parts of concepts, 40.7% of students experienced misconceptions, and 5.2% of students did not know the concept. The biggest misconception occurred in the subtopic frequency of simple harmonic motion by 75%, the relationship of the rope length with the pendulum vibration period by 60%, and 58.3% about the relationship between the total spring constant and the spring frequency. The instrument developed in this research was able to detect students' misconceptions, especially student learning experiences about simple harmonic motion